Pharmacokinetics and Relative Bioavailability of d‐Penicillamine in Fasted and Nonfasted Dogs. (22nd July 2013) - Langlois, D.K.; Lehner, A.F.; Buchweitz, J.P.; Ross, D.E.; Johnson, M.B.; Kruger, J.M.; Bailie, M.B.; Hauptman, J.G; Schall, W.D
Abstract : Background: d ‐Penicillamine is the most commonly used copper‐chelating agent in the treatment of copper‐associated hepatitis in dogs. Response to therapy can be variable, and there is a lack of pharmacokinetic information available for dogs. Coadministering the drug with food to alleviate vomiting has been recommended for dogs, which contradicts recommendations for drug administration to humans. Hypothesis: Coadministration ofd ‐penicillamine with food decreases relative bioavailability and maximum plasma drug concentrations ( C max ) in dogs. Animals: Nine purpose‐bred dogs with a median body weight of 17.0 kg. Methods: Dogs receivedd ‐penicillamine (12.5 mg/kg PO) fasted and with food in a randomized, crossover design. Blood samples were collected before and 0.25, 0.5, 1, 2, 3, 4, 8, 12, and 24 hours after dosing. Totald ‐penicillamine concentrations were measured using liquid chromatography coupled with tandem quadrupole mass spectrometry. Pharmacokinetic parameters were calculated for each dog. Results: Two fasted dogs (22%) vomited after receivingd ‐penicillamine. Mean C max ± standard deviation (SD) was 8.7 ± 3.1 μg/mL (fasted) and 1.9 ± 1.6 μg/mL (fed). Mean area under the plasma concentration curve ± SD was 16.9 ± 5.9 μg/mL·h (fasted) and 4.9 ± 3.4 μg/mL·h (fed). There were significant reductions in relative bioavailability and C max in fed dogs ( P < .001). Conclusions and Clinical Importance: Coadministration ofd ‐penicillamine with food significantly decreases plasma drug concentrations in dogs. Decreased drug exposure could result in decreased copper chelation efficacy, prolonged therapy, additional cost, and greater disease morbidity. Administration ofd ‐penicillamine with food cannot be categorically recommended without additional studies.